Ion-sensing properties of 1D vanadium pentoxide nanostructures - Vieira, Nirton C. S.; Avansi, Waldir [UNESP]; Figueiredo, Alessandra; Ribeiro, Caue; Mastelaro, Valmor R.; Guimares, Francisco E. G. (Springer, 2012)
The application of one-dimensional (1D) V2O5 center dot nH(2)O nanostructures as pH sensing material was evaluated. 1D V2O5 center dot nH(2)O nanostructures were obtained by a hydrothermal method with systematic control of morphology forming different nanostructures: nanoribbons, nanowires and nanorods. Deposited onto Au-covered substrates, 1D V2O5 center dot nH(2)O nanostructures were employed as gate material in pH sensors based on separative extended gate FET as an alternative to provide FET isolation from the chemical environment. 1D V2O5 center dot nH(2)O nanostructures showed pH sensitivity around the expected theoretical value. Due to high pH sensing properties, flexibility and low cost, further applications of 1D V2O5 center dot nH(2)O nanostructures comprise enzyme FET-based biosensors using immobilized enzymes.
Keywords: Vanadium pentoxide; Nanostructures; pH sensors; SEGFET; Hydrothermal synthesis